Development of Argumentation-Based Critical Thinking Skills Tests in Microbiology Laboratory - Evi Roviati; Ari Widodo; Widi Purwianingsih; Riandi Riandi (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2019)
This study aims to develop an instrument used to measure students' argumentation-based critical thinking skills (CTS) in microbiology practicum activities. This study used a phased model for the development of tools, which consists of the stages of defining constructs and formulating objectives in the form of mapping aspects of the critical thinking skills and the microbiology concepts, formulating test item formats, constructing item questions, constructing scoring guidelines, evaluating by experts for content validation, pilot testing on students and analyzing the results. The test items were then analyzed to determine the validity, reliability, distinguishing features and degree of difficulty. The instrument produced in this study used 6 CTS indicators which were considered the most relevant to argumentation and laboratory activities, and consisted of 18 open-ended questions with 5 contexts. The results of expert validation show that the instrument is content valid and can be used for the next step. Furthermore, the results of the pilot test show that of the 18 questions that were tested, as many as 17 questions were declared valid and 1 question was corrected. Overall the test questions were declared reliable. Thus, the results of this study recommend the use of questions on this test in studies that measure argumentation-based critical thinking skills in microbiology laboratory.